Time lapse microscopy is useful for elective single-embryo transfer. (2nd October 2016) - Haikin Herzberger, Einat; Ghetler, Yehudith; Tamir Yaniv, Rina; Berkovitz, Arie; Gonen, Ofer; Cohen, Ilan; Shulman, Adrian; Wiser, Amir
Abstract: The aim of our study was to evaluate time lapse microscopy (TLM) as a selection tool for single-embryo transfer (SET) on day 5, blastocyst stage. An observational cohort study was conducted. Patients who had SET were compared to patients who had double embryo transfer (DET). A total of 108 patients were included in analysis, 83 had SET, and 25 underwent DET. Embryos were incubated and evaluated using TLM. The pregnancy rates were similar between the groups (42.2% in SET and 48.0% in DET). However, the multiple pregnancy rate was significantly higher in the DET group compared to the SET group (41.7% versus 2.9%, respectively; p < 0.001). This study concludes that SET with TLM do not decrease pregnancy rates compared to DET. However, transfers of two embryos increase the rate of multiple pregnancies.